Detection of Acidic Pharmaceutical Compounds Using Virus-Based Molecularly Imprinted Polymers - Baek, In-Hyuk; Han, Hyung-Seop; Baik, Seungyun; Helms, Volkhard; Kim, Youngjun (MDPI, 2018)
Molecularly imprinted polymers (MIPs) have proven to be particularly effective chemical probes for the molecular recognition of proteins, DNA, and viruses. Here, we started from a filamentous bacteriophage to synthesize a multi-functionalized MIP for detecting the acidic pharmaceutic clofibric acid (CA) as a chemical pollutant. Adsorption and quartz crystal microbalance with dissipation monitoring experiments showed that the phage-functionalized MIP had a good binding affinity for CA, compared with the non-imprinted polymer and MIP. In addition, the reusability of the phage-functionalized MIP was demonstrated for at least five repeated cycles, without significant loss in the binding activity. The results indicate that the exposed amino acids of the phage, together with the polymer matrix, create functional binding cavities that provide higher affinity to acidic pharmaceutical compounds.